Plasma N-terminal tau fragment levels predict future cognitive decline and neurodegeneration in healthy elderly individuals - Chhatwal, Jasmeer P.; Schultz, Aaron P.; Dang, Yifan; Ostaszewski, Beth; Liu, Lei; Yang, Hyun-Sik; Johnson, Keith A.; Sperling, Reisa A.; Selkoe, Dennis J. (Nature communications, 2020)
The availability of blood-based assays detecting Alzheimer’s disease (AD) pathology should greatly accelerate AD therapeutic development and improve clinical care. This is especially true for markers that capture the risk of decline in pre-symptomatic stages of AD, as this would allow one to focus interventions on participants maximally at risk and at a stage prior to widespread synapse loss and neurodegeneration. Here we quantify plasma concentrations of an N-terminal fragment of tau (NT1) in a large, well-characterized cohort of clinically normal elderly who were followed longitudinally. Plasma NT1 levels at study entry (when all participants were unimpaired) were highly predictive of future cognitive decline, pathological tau accumulation, neurodegeneration, and transition to a diagnosis of MCI/AD. These predictive effects were particularly strong in participants with even modestly elevated brain β-amyloid burden at study entry, suggesting plasma NT1 levels capture very early cognitive, pathologic and neurodegenerative changes along the AD trajectory. Previously it was shown that an N-terminal tau fragment (NT1) measured in plasma can differentiate individuals with Alzheimer’s disease from healthy controls. Here the authors show that plasma levels of NT1 can associate with future cognitive decline in cognitively normal elderly individuals.